IFRS Convergence through PSAK 71: Constraining or Transforming Earnings Management? - Chandritike, Stevi Natasia; Yusnaini, Yusnaini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The convergence of Financial Accounting Standards (SAK) with International Financial Reporting Standards (IFRS) in Indonesia, particularly through the implementation of PSAK 71, is intended to improve the quality, transparency, and reliability of financial reporting through the Expected Credit Loss (ECL) approach. This forward-looking model enhances the timeliness of credit loss recognition and provides more relevant and decision-useful information for stakeholders. However, as a principle-based standard, PSAK 71 introduces a high degree of managerial discretion in determining key estimation parameters, which may create significant opportunities for earnings management practices. This study aims to examine whether PSAK 71 effectively constrains earnings management or instead transforms its underlying mechanisms. The research employs a Systematic Literature Review (SLR) of 22 peer-reviewed articles published between 2022 and 2025. The findings reveal inconsistent empirical evidence across prior studies. While some studies indicate improved transparency and a reduction in accrual-based earnings management, the majority of findings suggest a shift toward more complex and less observable forms, including estimation-based adjustments and real earnings management. The subjectivity inherent in ECL components increases the difficulty of detecting manipulation. Furthermore, the effectiveness of PSAK 71 is strongly influenced by corporate governance, audit quality, and institutional conditions. This study concludes that PSAK 71 does not eliminate earnings management but instead reshapes its mechanisms within financial reporting practices.